MPFL reconstruction: indications and results - Dall'Oca, Carlo; Elena, Nicholas; Lunardelli, Enrico; Ulgelmo, Maurizio; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: The medial patellofemoral ligament (MPFL) is the most important structure commonly injured during lateral patellar dislocation and its rupture accounts for 3% of total knee injuries. MPFL reconstruction (MPFLR) is a reliable procedure with good results but variable rates of recurrent instability. The aim of this study is to underline the proper indications for the MPFLR reconstruction and to explain all the pearls and pitfalls regarding the MPFLR both in our experience and found in the latest literature. Methods: A comprehensive search in the latest literature using various combinations of the keywords MPFL, MPFLR, dislocation, treatment was performed. The following data were extracted: diagnosis methods, indications and contraindications for isolated MPFLR, type of management, recurrence of instability, outcomes and complications. Results: History of multiple patellar dislocations is the most relevant indication for ligament reconstruction especially after a failed course of conservative treatment in presence of persistent patello-femoral instability. Gold standard technique for MPFLR has not been clearly defined yet. Conclusions: There is still poor literature about outcome comparisons, therefore it is challenging to decide which technique is the most appropriate as surgical procedures are continuously developing. The ideal candidates for MPFLR have to be decided after a throughout evaluation and careful planning and, with nowadays knowledge, it is possible to put indication for a reconstruction exposing the patient to minimal risks.